Thomas, A. (2024). The Politics and Ethics of Transhumanism. Techno-Human Evolution and Advanced Capitalism. Bristol University Press. - Rojas-Cortés, Nicolás (Journal of Posthumanism, 2024)
Criticisms of transhumanism are often as weak or even weaker than transhumanist proposals. If we consider that a significant number of criticisms arise from the fear of the dangers that technooptimistic proposals might pose to human nature—whatever that might mean—then the effectiveness of arguments against transhumanism is null. When technical production is effective, no one cares about the complaints of sages who are detached from the world we inhabit. In this sense, it is refreshing to find a systematic argument against transhumanism that does not rehash conceptual clichés that contribute little, especially when cutting-edge technology belongs to a few entrepreneurs who care little or nothing for the complaints reminiscent of the Vatican.